2016
DOI: 10.1111/pbi.12631
|View full text |Cite
|
Sign up to set email alerts
|

mlo‐based powdery mildew resistance in hexaploid bread wheat generated by a non‐transgenic TILLING approach

Abstract: SummaryWheat is one of the most widely grown cereal crops in the world and is an important food grain source for humans. However, wheat yields can be reduced by many abiotic and biotic stress factors, including powdery mildew disease caused by Blumeria graminis f.sp. tritici (Bgt). Generating resistant varieties is thus a major effort in plant breeding. Here, we took advantage of the non‐transgenic Targeting Induced Lesions IN Genomes (TILLING) technology to select partial loss‐of‐function alleles of TaMlo, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(128 citation statements)
references
References 50 publications
(77 reference statements)
7
118
2
1
Order By: Relevance
“…Mild temperatures (10–22 °C) further enhance the infection process (Beest et al , 2008). Upon adhesion of conidia or ascospores to a photosynthetically active wheat leaf surface, a specialized germ tube is produced and elongates to form a thread‐like hypha with appressoria and this process can complete within 2 hr (Acevedo‐Garcia et al , 2017). Shortly afterwards, the digitate hypha gives rise to a penetration peg and ramifies a haustorium to allow the breach of the host epidermal cell, via turgor pressure and dynamic enzymes (Glawe, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Mild temperatures (10–22 °C) further enhance the infection process (Beest et al , 2008). Upon adhesion of conidia or ascospores to a photosynthetically active wheat leaf surface, a specialized germ tube is produced and elongates to form a thread‐like hypha with appressoria and this process can complete within 2 hr (Acevedo‐Garcia et al , 2017). Shortly afterwards, the digitate hypha gives rise to a penetration peg and ramifies a haustorium to allow the breach of the host epidermal cell, via turgor pressure and dynamic enzymes (Glawe, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…TILLING was also employed to screen a mutant population of the Chinese wheat cultivar Sumai 3 in the map‐based cloning of Fhb1 , which confers head blight disease resistance (Rawat et al ., ). In addition, powdery mildew resistant wheat lines were developed using TILLING technology to select the mlo mutants (Acevedo‐Garcia et al ., ). The homozygous triple and double mutant lines showed enhanced resistance to powdery mildew without pleiotropic effects, suggesting that TILLING could be used to develop commercial wheat varieties.…”
Section: Modern Molecular Breeding Toolsmentioning
confidence: 97%
“…Recently, Acevedo Garcia et al [24] identified simultaneous mutations in the three wheat homologues of TaMlo, TaMlo-A1, TaMlo-B1 and TaMlo-D1 and produced homozygous triple and double mutant lines that showed increased resistance to powdery mildew. In another study, the knock-down of grapevine MLO genes (VvMLO7 in combination with VvMLO6 and VvMLO11) decreased powdery mildew severity up to 77 % [25].…”
Section: Introductionmentioning
confidence: 99%